Religious Freedom and Religious Equality: Research, Praxis, and Future Trajectories - Tadros, Mariz (The review of faith & international affairs, 2025)
This paper argues that the lexicon of religious equality has the potential to realize conceptual, paradigmatic, and policy inroads that contribute to making visible the day-to-day encroachments on freedom of religion or belief (FoRB). While mindful of the detrimental impact of diminishing support for international aid and multilateralism as well as deepening political polarizations domestically, the paper argues that a situated, intersectional approach to understanding drivers and outcomes of inequality has much to offer to religious freedom studies, in particular in how FoRB can practically serve as a driver for addressing marginalized people’s lived realities on the ground.